The effect of cleft lip on cognitive development in school-aged children: a paradigm for examining sensitive period effects. - Hentges, F; Hill, J; Bishop, D; Goodacre, T; Moss, T; Murray, L (John Wiley and Sons, 2011)
BACKGROUND: Our previous investigation showed that infants with cleft lip who had undergone late (three-month) surgical repair (but not those with early, neonatal, repair) had significantly poorer cognitive development at 18 months than a group of unaffected control children. These differences were mediated by the quality of early mother-infant interactions. The present study examined whether this pattern persisted into later childhood. METHOD: At 7 years, 93 index (44 early, and 49 late repair) and 77 control children were followed up and their cognitive development assessed (IQ, language and school achievements). RESULTS: Index children (particularly those with late lip repair) scored significantly lower than controls on tests of cognitive development. Group differences in Verbal IQ were mediated by 2 months' maternal sensitivity; this was associated with 7-year Verbal IQ, even after controlling for later mother-child interactions. CONCLUSIONS: Social interactions in the first few months may be of especial importance for child cognitive development. Interventions for infants with cleft lip should be directed at fostering the best possible parental care in infancy.